Uji Kuat Tekan Beton Mutu K375 dengan Direndam Selama 28 Hari - Mukti, Hasbi Bukhori; Abdulloh, Sayyid; Wicaksono, Adika; Humam, Sultan Paddy Nur; Nakulo, Seftian Bagus (JURNAL TEKNIK SIPIL, 2023)
This test evaluates the compressive strength of K-375 quality concrete after 28 days of immersion. Concrete is an essential material in construction due to its strength and durability, making K-375 quality concrete the primary choice for large-scale projects requiring high compressive strength, such as bridges, high-rise buildings, and industrial facilities. This study focuses on the impact of variations in concrete type and component proportions on the compressive strength of K-375 quality concrete. The test was conducted at the Civil Engineering Laboratory of Universitas Pelita Bangsa, using fine and coarse aggregates from Purwakarta. The study concludes that the selection, proportion of materials, and proper execution significantly affect the compressive strength of concrete, with most samples meeting national standards. This test contributes to optimizing concrete mixture design to meet the continuously increasing construction demands.